Teaching at the Right Level: Approaches and Implementations to Improve Secondary School English Student Learning Outcomes - Khulaifiyah, Khulaifiyah; Ahmad, Arimuliani; Iqbal, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effectiveness of the Teaching at the Right Level (TaRL) approach in improving student learning outcomes. TaRL is a teaching strategy that adapts instruction to students' actual ability levels, rather than their formal grade levels. This research method uses a quantitative approach with an experimental design. The study sample consisted of 39 high school students who were divided into intervention and control groups. The results showed that students in the TaRL group experienced significant improvements in their English sentence construction and pronunciation skills compared to the control group. These findings indicate that the TaRL approach can be an effective strategy in improving learning outcomes, especially for students with learning gaps.